1978
DOI: 10.1104/pp.62.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucuronokinase by Substrate Analogs

Abstract: Glucuronokinase from Llum lougMorum polen was purified 30-to 40-fold on a blue dextran-Sepharose column. Substrate analogs were tested for inhibitory effects, and nucleotide substrate specificity of the enzyme was determined. Nine nucleotides were tested, and al were inhibitory when the substrate was ATP. ADP was competitive with ATP and had a Ki value of 0.23 mm. None of the other nucleotide triphosphates could effectively substitute for ATP as a nucleotide substrate. Ten mm dATP and ITP reacted only 3% as ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Phosphorylation of GlcA also constitutes the myoinositol oxidation (MIO) pathway through which UDPGlcA is generated from myo-inositol via GlcA and GlcA 1-P. Glucuronokinase activity was first found in a soluble fraction of mung bean seedlings in 1959 (Neufeld et al 1959), and also reported in lily (Lilium longiflorum) pollens (Gillard and Dickinson 1978;Leibowitz et al 1977). Recently, Pieslinger et al purified the enzyme from lily pollens, and identified GlcAK gene encoding glucuronokinase in Arabidopsis (Pieslinger et al 2009(Pieslinger et al , 2010.…”
Section: Monosaccharide Kinasesmentioning
confidence: 99%
“…Phosphorylation of GlcA also constitutes the myoinositol oxidation (MIO) pathway through which UDPGlcA is generated from myo-inositol via GlcA and GlcA 1-P. Glucuronokinase activity was first found in a soluble fraction of mung bean seedlings in 1959 (Neufeld et al 1959), and also reported in lily (Lilium longiflorum) pollens (Gillard and Dickinson 1978;Leibowitz et al 1977). Recently, Pieslinger et al purified the enzyme from lily pollens, and identified GlcAK gene encoding glucuronokinase in Arabidopsis (Pieslinger et al 2009(Pieslinger et al , 2010.…”
Section: Monosaccharide Kinasesmentioning
confidence: 99%